Model simulasi pendekatan agent-based modeling untuk menganalisis angka buta huruf di Papua - Dicasani, Alifta; Chanafi, Galih Tri; Kusumawardanto, Aji; Munandar, Galih Mahardika (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The high illiteracy rate in Papua reflects significant social and economic challenges. This is largely due to the low educational participation rate in the region compared to the national average. Appropriate strategies are needed to support social and economic equity in Indonesia. This research aims to analyze the influence of education level, economic factors, and population on the high illiteracy rate using simulation. Agent-Based Modeling is used to simulate the interactions of these factors and understand their impact on the system. The results show that a combination of improved education quality and economic growth is a key factor in reducing illiteracy rates. Therefore, policy recommendations that consider the findings of this research are expected to support equity and development in Papua.